The effect of working capital management on profitability of listed manufacturing companies in Dar es salaam Stock Exchange (DSE) Tanzania - Shekalaghe, Kasimu (Mzumbe Unversity, 2024)
A research report for a dissertation to be submitted in partial fulfilment of the award of the Degree of Masters Science in Accounting and Finance (Msc. A&F) of Mzumbe University